Review of Afrotropical species of Goetheana Girault (Hymenoptera: Eulophidae), with description of a new species - Gumovsky, Alex (Zootaxa, 2016)
Three species of Goetheana Girault (Hymenoptera: Eulophidae, Entedoninae) are recorded from the Afrotropical biogeographic realm: G. shakespearei Girault (cosmopolitan), G. incerta Annecke (Namibia, South Africa, Swaziland, Uganda, Senegal) and G. kobzari Gumovsky sp. n. (South Africa, Uganda, Central African Republic). Goetheana incerta is re-described based on its type series, which is discussed. Males of G. shakespearei and G. incerta are easily separated by antennal scape structure, but females barely differ in morphology. New geographical records and a discussion of morphology of Goetheana are also provided.